Discourse strategies in the ‘Women Masters’ exhibition: A corpus study from Instagram - Rodríguez Cuadrado, Beatriz (Tendencias Sociales. Revista de Sociología, 2025)
Museums face serious challenges in addressing historical and systemic issues related to gender representation. Instagram has become a powerful tool for museums to engage with audiences, promote exhibits, and share their collection (Sarmiento Guede, 2021). This research focuses on analyzing the discourse of the ’Maestras’ exhibition in the Thyssen-Bornemisza Museum official Instagram account. This exhibition was opened in Madrid, on 31st October 2023 and closed on 4th February 2024. The objective of this multimodal study is to identify the communicative strategies on Instagram related to women in the role of an artist. The methodology follows a mixed approach. The sample includes all textual and audiovisual information published during the exhibition period. In the quantitative stage, we analyzed the keyword frequency and concordances using the textual tool ’Sketch Engine’. The qualitative approach involved an analysis of the discourse and language used by the institution on this social networking device. This framework contributes to demonstrate the new multimodal strategies that the Instagram provides in changing public perceptions and, consequently, steering society towards inclusion concerning gender. The results of this multimodal research will allow us to identify the strategies related to disseminating and promoting an exhibition where women are protagonists.